Effect of emotional freedom technique on the fear of childbirth in Iranian primiparous women: a randomized controlled trial - Emadi, Seyedeh Fatemeh; Hekmat, Khadijeh; Abedi, Parvin; Maraghi, Elham (Frontiers in Psychology, 2024)
Background: Fear of childbirth is one of the main causes of women’s emotional difficulty experienced in the perinatal period, especially those having their first child. Objective: The aim of this study was to investigate the effect of emotional freedom technique (EFT) on the fear of childbirth among primiparous women in Ahvaz, Iran. Material and Methods: This randomized clinical trial was conducted on 116 primiparous women. The participants were randomly divided into intervention (n = 58) or control (n=58) groups. The intervention group received daily stimulation of certain points in their body for 12 weeks using EFT. The fear of childbirth was measured at the beginning of the study and 12 weeks after the intervention using the Wijma Delivery Expectancy/Experience Questionnaire (WDEQ-A) and at the first postpartum visit with WDEQ-B. Data were analyzed using independent t-test, paired t-test, Chi-square or Fisher’s exact test, and analysis of covariance (ANCOVA). Results: After intervention, the mean score of fear of childbirth in the intervention group decreased from 49.39 ± 8.21 to 40.42 ± 13.43 (p<0.0001), while the same rate in the control group increased from 49.47 ± 9.06 to 52.09 ± 7.73 (p=0.002). The mean score of fear of childbirth after delivery in the control group (45.88 ± 7.10) was higher than that in the intervention group (27.13 ± 5.08) (p<0.0001). Conclusions: Based on the findings of this study, EFT can be considered as an effective method to reduce the fear of childbirth score in primiparous women.